Trade and Protection With Multistage Production - Dixit, Avinash K.; Grossman, Gene M. (Review of Economic Studies, 1982)
This paper analyses trade in manuf acutured goods that are produced via a vertical production structure with many stages, where some value is added at each to an intermediate product to yield a good-in-process ready for the next stage. We consider the stage at which a good is traded to be an economically endogenous variable, with comparative advantage determining the pattern of production specialization by stages across countries. We study how endowment changes and policy shifts move the margin of comparative advantage, which thus provides a channel for resource allocation adjustment that is additional to the usual ones of factor substitution and changes in the quantity of output.